Pengaruh Digital Marketing dan Online Customer Review Terhadap Keputusan Pembelian Mahasiswa Universitas Balikpapan di E-Commerce Shopee - Nur Sa’diyah; Nira Dewi Susanti; Riza Tri Permadi; Diah Anggraini; Syahril Hasan (Jurnal Ragam Pengabdian, 2026)
This study aims to examine how digital marketing and online customer reviews influence purchasing decisions. The data used in this study were obtained through questionnaires distributed to students at Balikpapan University. There were 167 respondents involved in this study. The sampling method used in this research is non-probability sampling. This study utilizes a Likert scale for measurement and analyzes the data using Smart PLS. Based on the research findings, it is concluded that digital marketing and online customer reviews have a positive effect on purchasing decisions on the Shopee e-commerce platform.